Anaphora — Exaltation or Offertory? - Милошевић, Ненад (Sabornost - The Theological Year-book, 2014)
The meaning, as well as the significance of notions exaltation (anaphora — ἀναφορά) and offertory (prosphora — προσφορά), along with other liturgical terms (placement — πρόθεσις, proscomidion προσκομιδή, even the Eucharist — εὐχαριστία), represented in the Eucharistic liturgies of the Eastern liturgical families, is still worth studying. The aim of this paper reflects an attempt to perceive different aspects of the same event that takes place in Anaphora, regardless of its structure. Although strikingly undistinguished moment that would suggest Ascension (ascendent epiclesis), highlighting descendent epiclesis in the Byzantine liturgy leaves no room for parsing events from the Economy of Salvation, because Christ is now the same, the Risen one, and Who ascended to heaven, and Whom the faithful receive in the Holly Communion. Clear emphasis, that the conversion of the Holy Gifts is done by the power and action of the Holy Spirit, at the same time marks the Resurrection and the Ascension and Pentecost.